2014
DOI: 10.1177/0009922814536924
|View full text |Cite
|
Sign up to set email alerts
|

Rehospitalization During the First Year of Life by Insurance Status

Abstract: Objective To assess the association of insurance status on infant rehospitalization in a population-based setting. Methods In this longitudinal retrospective study, hospitalizations were tracked for one year after birth discharge for 203,031 infants born in hospitals during 2008 using data from the New York State Inpatient Database. Relative risk was estimated using multivariable negative binomial regression models. Results Rehospitalization occurred in 9,010 infants (4.4%). Medicaid coverage and being uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…The New York SID also includes revisit variables that link multiple hospitalizations together to enable analyses of hospital readmissions. 13 These data have been used in previous studies evaluating trends in hospital readmissions among children 14 and adults. 15,16 We obtained data for live births in New York State from the New York Department of Health (http://www.health.ny.gov/statistics/vital_statistics/).…”
Section: Methodsmentioning
confidence: 99%
“…The New York SID also includes revisit variables that link multiple hospitalizations together to enable analyses of hospital readmissions. 13 These data have been used in previous studies evaluating trends in hospital readmissions among children 14 and adults. 15,16 We obtained data for live births in New York State from the New York Department of Health (http://www.health.ny.gov/statistics/vital_statistics/).…”
Section: Methodsmentioning
confidence: 99%
“…During the first year of life, 4.4% to 9.5% of term infants are rehospitalized, with Medicaid patients being at increased risk compared with those with private insurance. 4,5 Rehospitalization and ED visits are stressful to the family and costly to the payer. Common conditions leading to early newborn rehospitalization identified in previous studies include jaundice, feeding issues, and infection.…”
mentioning
confidence: 99%
“…The cut‐off of five days in our study for hyperbilirubinaemic infants, who often require exchange transfusion after initial phototherapy and periodic TSB monitoring would appear realistic and more cost effective in a resource‐limited setting. However, given the limited space available in the emergency department, this LHS threshold would have resulted in denied admissions for even more critical patients, as well as other adverse consequences of overcrowding . Lowering the threshold well below five days would be a worthwhile way to optimise care.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study in the United States reported that infants readmitted for hyperbilirubinaemia spent 0–155 days in hospital at an average cost of about $990 (median $819, range $300–$9727) per day . This would suggest that a long hospital stay (LHS) for this condition is associated with substantial emotional and economic burdens and has an impact on patient overcrowding , especially in resource‐limited settings . Overcrowding, resulting from an excess demand or need for urgent medical attention beyond the available resources, has been associated with such adverse outcomes as decreased physician productivity, poorer quality of emergency care, increased medical errors and lower patient satisfaction .…”
Section: Introductionmentioning
confidence: 99%